The 23rd International Electronic Conference on Synthetic Organic Chemistry 2019
DOI: 10.3390/ecsoc-23-06615
|View full text |Cite
|
Sign up to set email alerts
|

Halloysite Nanotubes Modified by Chitosan as an Efficient and Eco-Friendly Heterogeneous Nanocatalyst for the Synthesis of Heterocyclic Compounds

Abstract: In this study, halloysite nanotubes (HNTs) are modified by chitosan as a natural cationic amino polysaccharide. Halloysite nanotubes/chitosan (HNTs/Chit) were characterized by Fourier transform infrared (FT-IR) spectroscopy and energy dispersive X-ray (EDX) analysis. Also, its performance as a heterogeneous catalyst was investigated in the synthesis of pyranopyrazole derivatives. Being a reusable and easily recoverable catalyst, eco-friendliness, high efficiency, and mild reaction conditions are some advantage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Previous research has shown, a polysaccharide including Arabic Gum 20 , sodium alginate 21 , cellulose 22 , dextrin 23 , and chitosan 24 ; their modified forms were commnoly employed as main components of the different catalytic systems 25 27 . Additionally, a wide range of hydratererocylic compounds can be synthesized via catalysis using magneticnatural polymer composites, including magnetic guanidinylated chitosan (MGCS) nanobiocomposite 28 , HNTs/Chit catalyst 29 , Hyd AG-g-PAN/ZnFe 2 O 4 30 , and Fe 3 O 4 @xanthan nanocatalyst 31 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown, a polysaccharide including Arabic Gum 20 , sodium alginate 21 , cellulose 22 , dextrin 23 , and chitosan 24 ; their modified forms were commnoly employed as main components of the different catalytic systems 25 27 . Additionally, a wide range of hydratererocylic compounds can be synthesized via catalysis using magneticnatural polymer composites, including magnetic guanidinylated chitosan (MGCS) nanobiocomposite 28 , HNTs/Chit catalyst 29 , Hyd AG-g-PAN/ZnFe 2 O 4 30 , and Fe 3 O 4 @xanthan nanocatalyst 31 .…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, many commercial medicines and agrochemicals possess heterocyclic moieties [24]. Substantial efforts have been devoted into development of synthetic methods toward construction of heterocyclic compounds [25][26][27].In the continuation of our research program directed toward the development of new synthetic methods for the preparation of a variety of heterocyclic compounds via mild and environmentally benign conditions [28].…”
Section: Introductionmentioning
confidence: 99%